2003
DOI: 10.1111/j.1502-3885.2003.tb01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Laurentide and Cordilleran fast ice flow: some sedimentological evidence from Wisconsinan subglacial till and its substrate

Abstract: Dreimanis, A. 2003 (March): Laurentide and Cordilleran fast ice flow: some sedimentological evidence from Wisconsinan subglacial till and its substrate. Boreas, Vol. 32, With the aid of three case studies we summarize sedimentological and structural evidence in Wisconsinan subglacial till and its substrate that can be used to infer the presence of former fast-moving ice. We compare sedimentological characteristics of till with its stone fabric, stone surface erosional features and orientations of fractures, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…The simplest explanation is that the traction zone at the base of the A6 ice was effectively decoupled from the underlying cohesive bed (A5 deformation structure), either by a thin deformable bed, potentially represented by early soft sediment deformation within the Weybourne Town Till, or a veneer of pressurised water (Kjaer et al, 2006;Fischer et al, 2011). Basal conditions, such as those inferred here, often accompany fast or surging ice flow behaviour (Ó Cofaigh and Evans, 2001;Lian et al, 2003). Generic recognition of surging behaviour is provided by a range of sedimentological and landform features, however, few features on their own are unequivocally diagnostic of this type of flow mechanism (Evans et al, 1999;Evans and Rea, 1999;Evans and Rea, 2005;Evans et al, 2008).…”
Section: Bed Conditions During Initial Ice Advancementioning
confidence: 80%
“…The simplest explanation is that the traction zone at the base of the A6 ice was effectively decoupled from the underlying cohesive bed (A5 deformation structure), either by a thin deformable bed, potentially represented by early soft sediment deformation within the Weybourne Town Till, or a veneer of pressurised water (Kjaer et al, 2006;Fischer et al, 2011). Basal conditions, such as those inferred here, often accompany fast or surging ice flow behaviour (Ó Cofaigh and Evans, 2001;Lian et al, 2003). Generic recognition of surging behaviour is provided by a range of sedimentological and landform features, however, few features on their own are unequivocally diagnostic of this type of flow mechanism (Evans et al, 1999;Evans and Rea, 1999;Evans and Rea, 2005;Evans et al, 2008).…”
Section: Bed Conditions During Initial Ice Advancementioning
confidence: 80%
“…Classical fabric interpretation (e.g. Dowdeswell and Sharp, 1986;Hicock et al, 1996;Lian et al, 2003) would suggest that till genesis can be inferred from fabric strength and shape. However, laboratory results using a ring-shear device suggest that fabric strength is not unique to a specific genesis (Hooyer and Iverson, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere on Anglesey, this unit has been interpreted as glacitectonite produced by subglacial shearing and reworking of localised pre-existing bedrock and regolith . This subglacial interpretation is endorsed because of the high-consolidation of the diamicton, presence of striated and keel-shaped limestone clasts and a minor far-travelled lithological component (Boulton & Paul, 1976;Lian et al, 2003;Benn & Evans, 2010) observed in exposures at Beaumaris and Trwyn y Penrhyn (Section 3; Greenly, 1919). Scouring of the upper-surface of the basal diamicton to produce the deep sediment-filled scours is considered to have occurred by focussed meltwater incision of the subglacial bed.…”
Section: 1mentioning
confidence: 99%
“…Instead, the high consolidation of the diamicton, the presence of clasts from local and far-travelled sources plus the striated and keel-shaped limestone clasts are suggestive of subglacial till accretion (cf. Boulton & Paul, 1976;Lian et al, 2003;Benn & Evans, 2010). Flame-like margins along the base of the diamicton unit (Y1-Y2 scour) imply rapid loading and dewatering of the underlying basal lag.…”
Section: 1mentioning
confidence: 99%